The Problem of Altruism in the World and Ukrainian Pedagogy: the Historical Aspect - Stoiko, Kateryna (Pedagogical Discourse, 2018)
The article deals with the phenomenon of altruism from the point of view of pedagogy which consists of the fundamental understanding of it as an important personal quality. In this case, proposed the designation «altruism» is understood like an ethic principle and moral practice of concern for the happiness of other human beings, resulting in a quality of life both material and spiritual. The concept has a long history in philosophical and ethical thought. The term was originally coined in the 19th century by the founding sociologist and philosopher of science, August Comte. Category altruism was reflected in pedagogical science. Altruism is an ethical doctrine that holds that the moral value of an individual’s actions depend solely on the impact on other individuals, regardless of the consequences on the individual itself. Altruism focuses on a motivation to help others or a want to do well without reward. While ideas about altruism from one field can have an impact on the other fields, the different methods and focuses of these fields lead to different perspectives on altruism. The investigation presents different views on the interpretation and understanding of the problem of altruism and its importance in the educational process. The preconditions of entering the category of altruism in the world and domestic pedagogical thought are considered. The above-mentioned problem has been investigated in the historical aspect. The article proposes various ideas of leading teachers about the significance and role of altruism in the process of becoming an individual. In order to peculiarities of social realities of the mentioned historical epochs, we made the analysis of the problem of education of personality altruistic qualities based on a brief overview of historical and pedagogical literature. The generalization of the creative heritage of prominent representatives of foreign and domestic pedagogical thought, as well as their practical recommendations to the solution of the problem of education of altruistic qualities of an individual are made. The urgency of consideration of a problem at the present stage of educational work of pupils is considered.